The deglaciation of Barton Peninsula (King George Island, South Shetland Islands, Antarctica) based on geomorphological evidence and lacustrine records. (3rd September 2019) - Oliva, Marc; Antoniades, Dermot; Serrano, Enrique; Giralt, Santiago; Liu, Emma J.; Granados, Ignacio; Pla-Rabes, Sergi; Toro, Manuel; Hong, Soon Gyu; Vieira, Gonçalo
Abstract: Barton Peninsula is an ice-free area located in the southwest corner of King George Island (South Shetland Islands, Antarctica). Following the Last Glacial Maximum, several geomorphological features developed in newly exposed ice-free terrain and their distribution provide insights about past environmental evolution of the area. Three moraine systems are indicative of three main glacial phases within the long-term glacial retreat, which also favoured the development of numerous lakes. Five of these lakes were cored to understand in greater detail the pattern of deglaciation through the study of lacustrine records. Radiocarbon dates from basal lacustrine sediments enabled the reconstruction of the chronology of Holocene glacial retreat. Tephra layers present in lake sediments provided additional independent age constraints on environmental changes based on geochemical and geochronological correlation with Deception Island-derived tephra. Shrinking of the Collins Glacier exposed the southern coastal fringe of Barton Peninsula at 8 cal ky BP. After a period of relative stability during the mid-Holocene, the ice cap started retreating northwards after 3.7 cal ky BP, confining some glaciers within valleys as shown by moraine systems. Lake sediments confirm a period of relative glacial stability during the last 2.4 cal ky BP.